How Tamil Nadu Is Performing Better in Menstrual Hygiene Management in India: Evidence from National Family Health Survey (NFHS-4) - TP, Sherin Raj; Kathuria, Bhawna (International Journal of Human and Health Sciences (IJHHS), 2022)
Background:Menstruation is an integral part and natural process among women and it involved many myths, customs and misconceptions in India.Menstrual Hygiene Management (MHM) is a problem for young girls in India. Along with basic sanitation facilities, young girls and women need access to clean and soft, absorbent sanitary products for a long run and protect their health. In Tamil Nadu, India, menarcheof a girl is celebrated with the relatives and friends like a festival. Objective:This paper examines the initiatives taken by the state of Tamil Nadu of Indiaand the various factors associated with the menstrual hygienepractice among young women. Methods: Data collected from the 4th round of National Family Health Survey (NFHS-4), conducted in 2015-16 were used for analysis. The sample consists of 14,949 young women in the age group of 15-24 years who have ever menstruated. Results: The state government’s initiatives, series of activities, interdepartmental collaboration and coordination, participation of civil society and community helped Tamil Nadu state to perform in a better manner.The resultsreveals the odds for women in the richest quintile, higher education, living in urban areas with higher awareness and availability of flush toiletsgive higher odds ratio determining the factors associated with the usage ofhygienic methods. Conclusion: For better menstrual hygiene it requires a very good knowledge and awareness on menstrual cycle, hygiene essentials, safe and secure sanitary products and good water, sanitation and hygiene (WASH) facilities. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 404-411